The use of gadolinium-based contrast agents in Ghana with a focus on residual intracranial gadolinium deposition. Issue 3 (August 2018) - Piersson, A.D.; Gorleku, P.N.
Abstract: Introduction: The aim of the survey was to identify current practice of the use of gadolinium-based contrast agents (GBCAs) in the wake of recent reports on gadolinium deposition in the brain following repeated administration of GBCAs. Method: A total of 13 facilities in Ghana with magnetic resonance imaging (MRI) departments were contacted via email with a two-page questionnaire. Results: A response rate of 69.2% (n = 9) was achieved. Gadodiamide (Omniscan) was the most commonly used GBCA. Slightly more than half of respondents were aware of residual deposition of GBCAs in the brain. Majority of the respondents were aware of GBCA deposition in individuals with abnormal renal function, but not aware of its deposition in those with normal renal function. A great majority of the respondents do not record the type and dose of GBCA after each intravenous administration, and such information is not provided in MRI reports. More than half of the respondents do not check eGFR prior to the administration of GBCA even when a high-risk agent is used. Conclusion: Gadodiamide (Omniscan) a high-risk agent remains the most commonly used GBCA in Ghana. Awareness of current findings of GBCA deposition in the brain following repeated doses are not encouraging as revealed in this study. The need to adopt international standard guidelines into practice cannot be overemphasized in order to reduce the potential long-term effect of this deposition. Highlights: Gadodiamide (Omniscan) was the most commonly used GBCA in Ghana. Most were unaware of gadolinium deposition in individuals with normal renal function. Most respondents do not record the type and dose of GBCA after administration. Protocols lacked information on gadolinium deposition in the brain.